Elastisitas Jasa Kereta Api Bandara Kualanamu (Airport Railink Service) - Puspitasari, Mariana Diah; Istiantara, Dedik Tri (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2018)
In July 25th, 2013 Indonesia for the first time provided rail link service from and to an airport. It particularly was operated from and to Kualanamu International Airport (KNIA), Deli Serdang, North Sumatera, which was also operated for the first time on that date. Managing the airport rail link service, a private company namely PT. Railink basically is the subsidiary company of PT. Angkasa Pura II (Persero) and PT. Kereta Api Indonesia (Persero). The price of train ticket, in fact, is getting higher as time goes by. It is noted that the ticket price has increased from IDR 80K to IDR 100K since January 15th, 2015. Concerning this situation, this study is conducted to investigate the demand elasticity of the airport rail link service from and to Kualanamu International Airport as well as factors in taking the airport rail link. The result of the study reveals that the demand of airport rail link service as the impact of the increasing of the ticket price is inelastic since its value of elasticity reaches -0.38. The other result, moreover, finds six reasons influencing people to go with airport rail link: comfort, punctuality, speed or travel time, practicality, access to train station, and other modes’ tariff.